2(-7a+6)=-16a-7a

Simple and best practice solution for 2(-7a+6)=-16a-7a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-7a+6)=-16a-7a equation:


Simplifying
2(-7a + 6) = -16a + -7a

Reorder the terms:
2(6 + -7a) = -16a + -7a
(6 * 2 + -7a * 2) = -16a + -7a
(12 + -14a) = -16a + -7a

Combine like terms: -16a + -7a = -23a
12 + -14a = -23a

Solving
12 + -14a = -23a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '23a' to each side of the equation.
12 + -14a + 23a = -23a + 23a

Combine like terms: -14a + 23a = 9a
12 + 9a = -23a + 23a

Combine like terms: -23a + 23a = 0
12 + 9a = 0

Add '-12' to each side of the equation.
12 + -12 + 9a = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 9a = 0 + -12
9a = 0 + -12

Combine like terms: 0 + -12 = -12
9a = -12

Divide each side by '9'.
a = -1.333333333

Simplifying
a = -1.333333333

See similar equations:

| x^2+24x+144-y^2= | | 4-2x+10=5-6x | | 5(x-6)=-2(3-x) | | 0.12(18)+0.02x=0.06(6+x) | | 2x^2+22x+85=0 | | 6+3x=2-4x | | (3x+20)=x | | x-4+5-y= | | -3x+7=43 | | 8(t-6)+4=4(3t+5)-9 | | ln(8+x)=3 | | 3x-4(c-5)-2(y-6)= | | (-4r^3)(8r^2+7)(8r^2-7)= | | (4b-5f)(4b+4f)= | | (9-u)(5+5u)= | | (3x+6)(2x+3)= | | (4x+7)(4x-5)= | | 30x^3+51x^2-60x= | | (r+4)(r-2)= | | (5t^2-t-5)(2t^2+5t-1)= | | (x^3+x^2+x+1)(15x-4)= | | (9x+4)(6x^2+9x+5)= | | 9x^2(x^2+6xy-7y^2)= | | (9x^2)(x^2+6xy-7y^2)= | | (4x^3)(2x^2-4x+4)= | | 4x^3(2x^2-4x+4)= | | (5x)*(-9x^3+6x^2)= | | (5x+3)=(3x-7) | | .30*80+.60x=.40*80+.40x | | 50=(3x-1) | | 3a+7a= | | 0.36(18)+0.06x=0.12(6+x) |

Equations solver categories